Chronic nitrate enrichment decreases severity and induces protection against an infectious disease. (May 2016) - Smallbone, Willow; Cable, Jo; Maceda-Veiga, Alberto
Abstract: Excessive fertilisation is one of the most pernicious forms of global change resulting in eutrophication. It has major implications for disease control and the conservation of biodiversity. Yet, the direct link between nutrient enrichment and disease remains largely unexplored. Here, we present the first experimental evidence that chronic nitrate enrichment decreases severity and induces protection against an infectious disease. Specifically, this study shows that nitrate concentrations ranging between 50 and 250 mg NO3 − /l reduce Gyrodactylus turnbulli infection intensity in two populations of Trinidadian guppies Poecilia reticulata, and that the highest nitrate concentration can even clean the parasites from the fish. This added to the fact that host nitrate pre-exposure altered the fish epidermal structure and reduced parasite intensity, suggests that nitrate protected the host against the disease. Nitrate treatments also caused fish mortality. As we used ecologically-relevant nitrate concentrations, and guppies are top-consumers widely used for mosquito bio-control in tropical and often nutrient-enriched waters, our results can have major ecological and social implications. In conclusion, this study advocates reducing nitrate level including the legislative threshold to protect the aquatic biota, even though this may control an ectoparasitic disease. Graphical abstract: Highlights: Ecologically and legally relevant nitrate levels control an infectious disease. First report that nitrate does not act as an immune-suppressor in vertebrates Nitrate kills a species used for mosquito biocontrol in nutrient enriched waters. Current safety nitrate threshold (50 mg/l) can be lethal to aquatic fauna.